Education in Lebanon: Considerations and Evolution - NASSAR Chirine (Applied Research in Administrative Sciences)
The present study aims to investigate the perception regarding the education system in Lebanon and its impact on the communities’ development. The research methodology consists of a survey conducted among alumni from different types of schools. The study uses quantitative research methods to investigate the role of education for the development of society. The research instrument used was a questionnaire designed by the author based on previous studies that investigated the perception of education’s role in the development of society. The main findings of the study suggest that in Lebanese society, education has a significant impact as well as a strong need for education facilities and an increase in the budget spent by the government on the education field.